MATHEMATICAL MODEL OF THE HYDRAULIC CUTTER DRIVE FOR CUTTING AND UNLOADING THE BLOCK-PORTION OF FEED FROM THE FEED MONOLITH - VRUTKEVYCH, Volodymyr; KUSHNIR, Vitaly; GANZHA, Vadim (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The question of improving the efficiency and quality of separating and unloading a block portion of stem fodder from a fodder monolith in a trench storage is under consideration. Modern trends in the development of equipment for unloading stalk fodder from trench storages are analyzed. A fundamentally new design and technological scheme of the cutter for separating and unloading a portion block from a fodder monolith is presented, which allows for the process of unloading stem fodder from trench storages in accordance with zootechnical requirements and taking into account the variable technological load on the working organs of the cutter. The main advantages of using a hydraulic drive on this type of equipment and a certain disadvantage are indicated: separate hydraulic motors of the drive of the cutting mechanism of the separator and the hydraulic cylinder of the feed drives, which lead to the use of hydraulic motors of overpowered power.A hydraulic drive and a mathematical model of the hydraulic drive of the cutter for the separation and unloading of silage from trench storages have been developed, which allows you to coordinate the operation of the drive of the knife mechanism with its feed. The use of the proposed hydraulic drive will ensure optimal feeding of the knife mechanism and protection of the hydraulic motor from overload. This is due to the fact that when cutting off the stem forage from the forage monolith, conditions arise (freezing, variability of the fractional composition and moisture content of the forage, ingress of foreign objects, etc.) when it is necessary to adjust the feed of the knife mechanism.This task is solved due to the fact that the liquid pumped by the pump is evenly distributed by the volumetric flow divider between the hydraulic motor of the blade mechanism drive and the rotating hydraulic cylinder of the blade mechanism feed. If necessary, the feed of the knife mechanism is controlled by an adjustable throttle, which partially diverts the liquid to the tank from the injection cavity of the line of the rotary hydraulic cylinder.
Keywords: silo; trench; working body; hydraulic drive; mathematical model; hydrocylinder; hydromotor; change of drive